(3GdCSQGQ GdehOYI aj HYV UhQ GdbQBf GdcQjes
(3ChdgG (B:s
(3GdMeO ddg GdPi VGbJ SQGObGJ GdYQT Yf bHGH LdGdg hHYO agPg QSGdI YedJgG ai GdJfHjg Ydi HYV GdCSQGQ GdehOYI ai HYV ShQ GdbQBf GdcQje s
(3BNQgG (B:s
(3Edi ChL GdSYGOI hGdceGd aEfg dGjUd Zdjg GdEHeLehY gPg GdCMhGd GdCQHYI aUGQ gPG XGgQ gPg GdShQ hGdMeO ddg QH GdYGdejf s
(3Vef eLehY , JQJjHgG (B: (3GdQGHY YTQs
(3GdfSNI HgG MhGTs
(3GfXQ GdeNWhW Qbe (B292s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJaSjQ hYdhe GdbQBfs